Comparable viral decay with initial dolutegravir plus lamivudine versus dolutegravir-based triple therapy. (30th April 2019) - Gillman, Jason; Janulis, Patrick; Gulick, Roy; Wallis, Carole L; Berzins, Baiba; Bedimo, Roger; Smith, Kimberly; Aboud, Michael; Taiwo, Babafemi
Abstract: Objectives: To expand understanding of the virological potency of initial dolutegravir plus lamivudine dual therapy (dolutegravir/lamivudine), we compared the viral decay seen in the pilot ACTG A5353 study with the decay observed with dolutegravir plus two NRTIs in the SPRING-1 and SINGLE studies, while also exploring the impact of baseline viral load (VL). Methods: Change in VL from baseline was calculated for timepoints shared by A5353 ( n = 120, including 37 participants with pretreatment VL >100000 copies/mL), SPRING-1 ( n = 51) and SINGLE ( n = 417). The 95% CIs of change from baseline were determined for each observed week, using the mean log10 -transformed VL, and compared between the dolutegravir/lamivudine and triple therapy groups using the Wilcoxon Rank Sum test for non-inferiority (δ = 0.5). To assess the impact of baseline VL on viral decay, we examined a bi-exponential non-linear mixed-effect model. Results: The mean VL change from baseline to week 24 was −2.9 log10 copies/mL for dolutegravir/lamivudine versus −3.0 log10 copies/mL for dolutegravir-based three-drug therapy ( P < 0.001). In the decay model, baseline VL >100000 copies/mL was associated with a slower initial decay rate ( d 1 ). A faster initial decay rate was seen with dolutegravir/lamivudine, which was partially offset when baseline VL was >100000 copies/mL as indicated by a significant interaction between baseline VL and drug therapy group. The secondary decay rate ( d 2 ) was not significantly different from zero, with no significant associations. Conclusions: Viral decay with dolutegravir/lamivudine was comparable to viral decay with dolutegravir-based triple therapy, even in individuals with higher pretreatment VL (>100000 copies/mL).